The emergence of collective moral elevation through multilevel individual and organizational processes - Marasli, Furkan; Golgeci, Ismail; Akgun, Ali Akber; Muceldili, Busra; Arslan, Ahmad (EMERALD GROUP PUBLISHING LTD, 2025)
Practical implications - This model emphasizes the pivotal role of student empowerment, an educational approach that not only enhances students' proficiency in community development potentially shapes their career trajectories, as evidenced by the case projects examined in this study. this model offers HEIs a structured pathway to enrich student engagement in realizing SDGs initiatives. It posits student empowerment as the foundational element, fostering a learning environment students gain valuable skills and insights into community development, potentially guiding professional endeavors. This research provides practical direction for those HEIs implementing which will increase the positive impacts brought by HEIs, especially for the students and local community. Originality/value - To the best of the authors' knowledge, no previous studies have proposed model specifically designed to engage students in achieving SDGs through USR programs in The significance of this study lies in its potential to serve as a guide for higher education institutions enabling them to effectively leverage USR programs to contribute toward SDGs. This makes invaluable resource for researchers, policymakers and educators who are committed to fostering
Keywords: Collective; Elevation; Emotions; Moral; Organizations; Process; GRAND CHALLENGES; PERSONAL NORMS; BEHAVIOR; EXCHANGE; GRATITUDE; WORK; PSYCHOLOGY; EXPERIENCE; EMULATION; Business & Economics